Studi Penambahan Daun Kalakai (Stenochlaena palustris) terhadap Nilai Gizi dan Sifat Organoleptik Kaki Naga Ikan Toman (Channa micropeltes) - Tyas Wara Sulistyaningrum; Evnaweri Evnaweri; Hasriani Sitanggang (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2022)
This study aims to determine the effect of adding different kalakai leaves (Stenochlaena palustris) to the quality of the toman fish (Channa micropeltes) drumstick. Drumstick is a type of nugget served in a round or oval shape and attached to an ice cream stick. This research activity includes chemical tests (moisture content, protein content, fat content, carbohydrate content, crude fiber content, and ash content) which were carried out at the Fish Nutrition Laboratory of the Bogor Agricultural University and organoleptic tests were carried out at the Fisheries Product Technology Laboratory, University of Palangka Raya. The design used was a completely randomized design (RAL) with 4 stages of treatment with the amount of ground fish meat in one treatment of 400 g. Some of the treatments were treatment A (kalakai 200 g) as control, treatment B (kalakai 250g), treatment C (kalakai 300 g), and treatment D (kalakai 350 g). The average results of the chemical test of the best treatments for moisture content were treatment A (58.31), Ash D (1.89), protein C (5.96), fats A and C (2.75), carbohydrates B (24.98) and crude fiber B (0.61). The best treatment for organoleptic test was color A (6.8), scent B (6.56), taste B (6.68) and texture A (6.64). The results of the best treatment using the effectiveness index, namely treatment D with the addition leaves of kalakai (Stenochlaena palustris) of 350 g, which is 0.681. Keywords : Leaves of kalakai, nutritional and organoleptic, toman, drumstick